Campaña de lanzamiento de empila, bebida Ready to Drink (RTD) - Hoffmann Macassi, Ximena Xiomara (2025)
Empila is a new ready-to-drink (RTD) beverage set to enter the Peruvian market in October 2025, targeting young adults between the ages of twenty and forty from socioeconomic levels B and C. The launch will focus on five key cities: Lima, Arequipa, Trujillo, Chiclayo, and Cusco. The development of this campaign is based on a market and consumer behavior analysis, which reveals a growing preference for products that combine convenience, authenticity, and alignment with a modern lifestyle. The target audience values naturalness, holistic well-being, and social connection. In this context, Empila positions itself as an option that aligns with their interests and aspirations. The strategy aims to achieve brand awareness of 50% and capture 8% market share by the end of the year. To achieve this, a comprehensive 360° campaign will be implemented, including digital media, point-of-sale activations, and collaborations with content creators. Beyond the product, Empila is positioned as a choice that resonates with consumers seeking authenticity and well-being in their daily lives.